DIAGNÓSTICO DE LA APLICACIÓN DE NORMAS DE BIOSEGURIDAD EN GRANJAS AVÍCOLAS DEL CANTÓN QUEVEDO Y SU ÁREA DE INFLUENCIA - Sánchez Llaguno, Ahelis Michelle (2023)
Biosecurity and animal hygiene are fundamental pillars of poultry health, with the rational application of technology, hygiene procedures, and work standards to prevent infectious agents from entering poultry farms and from these to other farms. The objective of this research work was to verify the application of biosafety standards in poultry farms in the Quevedo canton and its area of influence. The study was carried out in the province of Los Ríos canton Quevedo.